PROFESSIONAL ETHICS OF CIVIL SERVANTS AS PUBLIC SERVANTS CASE STUDY OF ONE-DOOR INTEGRATED SERVICES AT THE MANDAILING NATAL DISTRICT PROSECUTOR'S OFFICE BRANCH IN NATAL - Ari Antonius Sibarani; Debby Yohanna; Gani Gemilang; Kharisda Novtri Gratia Gulo; Miftahul Jannah Rahmatus Sani Simatupang; Dito Aditia Darma Nst (Universitas Efarina, 2025)
This study aims to analyze the legal basis for public services and the State Civil Apparatus, as well as the implementation of the One-Stop Integrated Service (PTSP) at the Mandailing Natal District Attorney's Office Branch in Natal. This study uses a normative research method with a legislative and conceptual approach, while data is collected through a literature review of laws, technical regulations, institutional documents, scientific journals, and other relevant literature. The focus of the research is directed at examining Law Number 25 of 2009 concerning Public Services and Law Number 20 of 2023 concerning State Civil Apparatus as a normative framework that regulates the principles of transparency, accountability, professionalism, and good governance in the provision of public services. The results of the study indicate that normatively, both laws have provided a strong foundation for the implementation of a quality PTSP and are oriented towards improving legal services. However, the implementation of PTSP at the Mandailing Natal District Attorney's Office Branch still faces several obstacles, including limited human resources, less than optimal use of information technology, inadequate service facilities, and weak guarantees of certainty regarding service time and costs. Furthermore, the non-issuance of a Government Regulation as the implementing regulation for the 2023 Civil Servant Law creates legal uncertainty that could potentially hinder the consistency of the service system. Overall, this study concludes that while the One-Stop Integrated Service (PTSP) has had a positive impact on service effectiveness, regulatory improvements, increased human resource capacity, and facility optimization are needed to ensure more professional, efficient, and integrated public services within the prosecutor's office.